2014
DOI: 10.1007/128_2014_607
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding in Solution

Abstract: Because of its expected applicability for modulation of molecular recognition phenomena in chemistry and biology, halogen bonding has lately attracted rapidly increasing interest. As most of these processes proceed in solution, the understanding of the influence of solvents on the interaction is of utmost importance. In addition, solution studies provide fundamental insights into the nature of halogen bonding, including, for example, the relative importance of charge transfer, dispersion, and electrostatics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 134 publications
(87 reference statements)
0
45
0
Order By: Relevance
“…In contrast, increasing the size and positive nature of halogen's '-hole' dramatically enhances the strength of the electrostatic component of the halogen bonding interaction [50,51]. Moreover, despite a purely electrostatic model is insufficient for the description of halogen bonds in polar systems, it may give reasonable correlation to experimental data obtained in non-polar medium [16].…”
Section: Electrostatic Potential Surfaces (Epss)mentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, increasing the size and positive nature of halogen's '-hole' dramatically enhances the strength of the electrostatic component of the halogen bonding interaction [50,51]. Moreover, despite a purely electrostatic model is insufficient for the description of halogen bonds in polar systems, it may give reasonable correlation to experimental data obtained in non-polar medium [16].…”
Section: Electrostatic Potential Surfaces (Epss)mentioning
confidence: 92%
“…In fact, several studies applying IR spectroscopy, X-ray diffraction, solid state NMR, and computational modelling confirmed that alcohols can form HBs with the C O and NH functions of the polymer, resulting in a change of the polymer structure with respect to the presence of Hex [40]. On the other hand, solvents possessing HB donor functionalities destabilize all types of XBs, primarily because of halogen vs hydrogen bond competition [16]. On this basis, taking into account that the strength of polar interactions decreases following the order Hex EtOH > MeOH, whereas the strength of the hydrophobic interactions follows the opposite order, polar and hydrophobic contribution to enantioseparation could be evaluated separately.…”
Section: Halogen-dependent Enantioseparationsmentioning
confidence: 93%
“…Although similar from the viewpoint of formation to hydrophilic hydrogen bond (HB), the XB is of hydrophobic nature, and this complementarity provides new opportunities for molecular recognition, particularly in solvated environment. Nevertheless, the exploration of solvent effects on XB has begun later compared to solid‐state studies, and to date the applications in solution are still challenging . Indeed, formation and detection of XBs in solution are more complicated as compared to the solid state because the interactions can be influenced by conformational freedom of the molecules, a less ordered medium, and solvent effects on both donor and acceptor .…”
Section: Introductionmentioning
confidence: 99%
“…Halogen bonds are frequently studied using nitrogen compounds, which typically display monovalent N···X (X = I, Br) interactions and are well understood as crystal engineering tools for self-assembly processes. Their precedence from discrete structures to increased dimensionality through the controlled reactivity of substrates is well-reported [10][11][12][13]. In a solid-state XB complex, R−X···B−Z, where X is the donor and B is the acceptor atom, the ratio of the short distance between X and B atoms (d X-B ) to sum of the Van der Waals radii of X and B atoms (d vdW ) is defined as the normalized strength parameter, R XB = d X-B /d vdW [1].…”
Section: Introductionmentioning
confidence: 99%